1989
DOI: 10.1111/j.1365-2591.1989.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method for comparing the effcts of different root canal preparation techniques on the shape of curved root canals

Abstract: This study introduced an in vitro model which was designed to observe the effects of instrumentation on the shape of curved root canals. The model may be accurately rotated through 90 degrees allowing reproducible radiographs to be taken from two different angles. The root canals were filled with a radiopaque contrast medium before radiographs were taken. Two-dimensional evaluation of the shape of the root canals, before and after preparation was made on enlarged photographic prints obtained from the radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A previously established radiographic technique was used in this study ( Tang & Stock 1989, Abdo 1994), but modified according to Luiten et al . (1995) to use mercury in order to enhance contrast and eliminate the problem of removal of isopaque.…”
Section: Discussionmentioning
confidence: 99%
“…A previously established radiographic technique was used in this study ( Tang & Stock 1989, Abdo 1994), but modified according to Luiten et al . (1995) to use mercury in order to enhance contrast and eliminate the problem of removal of isopaque.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ultrasonically or sonically prepared teeth have significantly cleaner canals than teeth prepared by hand instruments (14,(147)(148)(149)(293)(294)(295)(296). Numerous studies have analyzed the different characteristics of ultrasonically activated files, such as cutting efficiency (11,12,(297)(298)(299)(300)(301)(302), effect on bacteria (168,303,304), characteristics of root canal preparation (153,(305)(306)(307)(308)(309)(310)(311)(312)(313), mechanical and technical features of files and handpieces (314 -318), and clinical implications (319 -323).…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…The amount of the residual opaque medium remaining in the canal following preparation demonstrates the areas of insufficient cleaning (Littman 1977). Other experiments using radiopaque materials to visualize root‐canal morphology have also been conducted (Mayo et al . 1986, Tang & Stock 1989, Scarfe et al .…”
Section: Introductionmentioning
confidence: 99%